Drought monitoring of large lakes in Iraq using remote sensing images and normalized difference water index (NDWI) - Mohammed R. Mahmood; Baydaa Ismail Abrahem; Huda J. Jumaah; Hayder A. Alalwan; Malik M. Mohammed (Results in Engineering)
Drought conditions bring many problems to water resources, especially in areas of low precipitation. This study employs the Normalized Difference Water Index (NDWI) to understand the severity of drought for effective and sustainable utilization and timely response. The research uses image processing techniques to calculate surface water area with its changes for three essential lakes in Iraq (Haditha, Therthar, and Razzazah) during two time periods from 1987 to 2000, and from 2000 to 2014. Furthermore, Support Vector Machine (SVM) method was applied on Sentinel-2 images for 2024 to recognize the current changes in the three lakes. The analysis was based on the Geographic Information Systems (GIS) spatial analyst tool and Landsat images by building and executing a single map algebra expression of NDWI based on Python syntax. A drastic change occurred for the Razzazah lake surface area which increased by 2.5 % from 1987 to 2000 and decreased by 67 % from 2000 to 2014. The total decrease in Therthar and Haditha lakes from 1987 to 2014 was 28 %, and 12.6 %, respectively. There were slight changes in the geomorphological shape of Haditha Lake. While, Razzazah Lake underwent a noticeable change in shape, represented by a decrease in the northern and eastern parts of the lake. Therthar Lake has also been subjected to a reduction and change in the northern part with total drying up of lake parts in the southeast which turned to bare land. The study provides methodological guidelines for effective water management in the areas of Iraq requiring immediate interventions.